You are on page 1of 1

1

)
)
2

24+
= 4 2 = 8 = 6
1+1
) x + 1 0 x 1 . A = { 1}
) g (1) = 4

2 x 2 4 x 6 2( x 2 2 x 3)
.
=
x +1
x +1

) g ( x) =

x 2 2 x 3 = 16 x1,2 =

24
x = 3 x = 1
2

x 2 2 x 3 = ( x 3)( x + 1)
2( x 3)( x + 1)
= 2( x 3) .
g ( x) =
x +1
3
x >0

) : (2 x + 2) 2 = x(5 x + 8) .... x 2 = 4 x = 2
) x = 2 a1 = 2 a2 = 6 .
2 6
= =3
=
1 2
) S6 = 2

36 1 6
= 3 1 = 728
3 1

4
) =0 : 2 x 2 = 0 x = 1
) i) 0
= 2 ( 1) 4 ( 2) = 4( 2 2 + 1) 4( 2 2 ) = ... = 4
2

2( 1) 2 2 + 2 2
=

2
2
2 + 2 2 2
x1 =
=
= 1
2
2

2 + 2 + 2 2 + 4 2( 2) + 2 2
2
x2 =
=
=
=
=
+ = 1 +
2
2
2

:
2
2

x1 x2 > 1 1 1 + > 1 > 1

x1,2 =

ii)

>0
2
> 1 < 2 2 < < 2

0 (2, 0) (0, 2)